Legal Certainty on The Implementation of Electronic Registration of Liability Rights Performed by The Office of The Land Act Maker (Study at the Office of the Land Act Maker Deli Serdang) - Nasution, Dicky Kurniawan; Fauzi, Ahmad; Ruslan, Ruslan (Veteran Law Review, 2021)
Problem of legal certsinty on registration of liability rights performed by the office of the land act maker because there is a regulation from the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia has issued Ministerial Regulation Number 5 of 2020 concerning Electronically Integrated Mortgage Services. This research uses normative legal research, which includes research on legal principles, research on legal systematics, research on the level of legal synchronization, research on legal history and comparative legal research. In this study, the approach used is a statute approach, namely an approach using legislation and regulations. The results of the discussion in which the electronic mortgage registration process is based on the provisions of Article 9 of the Regulation of the Minister of Agrarian and Spatial Planning / National Land Agency (ATR / BPN) Number 5 of 2020, explains a creditor in applying for mortgage services through the HT-el system provided by Ministry of Agrarian Affairs and Spatial Planning / National Land Agency (ATR / BPN). In the event that the application for HT-e services is in the form of a Mortgage registration or a transfer of Mortgage Rights, the PPAT must submit the required documents. Furthermore, in the event that the application for HT-el Services is in the form of a change in the name of the creditor, the abolition of the Mortgage Right, or correction of data, the required documents shall be submitted by the creditor. Furthermore, the requirements for application for HT-el Services are in accordance with the provisions of laws and regulations and are submitted in the form of an Electronic Document. The obstacles for PPAT in registering HT-el, include negligence, server interference, creditors not yet registered and not validated in the Electronic HT service system. Â